Implementasi Manajemen Strategik dalam Meningkatkan Mutu Tenaga Pendidik Di MAN I dan MAS Al Muhsin Metro Lampung - Sujino (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This article mainly focuses on the strategy formulation, implementation, and evaluation stages in MAN and MAS Lampung. This research is qualitative-descriptive research. The data sources are the head of the Madrasah, the deputy head of the Madrasah, and teacher representatives. Data collection was done by interview, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The data validity test used the triangulation technique. The results showed that first, the strategy formulation phase is carried out by formulating a vision, mission, and goals based on the results of a study of the objective conditions of the internal and external environment, then formulating a strategic plan and Madrasah profile. Second, the strategy implementation stage is carried out by elaborating the strategy formulation into the activities of organizational structure preparation, Division of tasks according to qualifications and competencies, socialization of Madrasah potential and teaching staff, implementation of education and training, carrying out further studies, allocating teacher quality improvement budget, and carrying out development and mutation of teacher career improvement. The third evaluation stage of the strategy is carried out through teacher competency tests, teacher performance assessments, and teacher certification.